2013
DOI: 10.1016/j.pbb.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential development of tolerance to the functional and behavioral effects of repeated baclofen treatment in rats

Abstract: Baclofen, a gamma-aminobutyric acid (GABA)B receptor agonist, has been used clinically to treat muscle spasticity, rigidity and pain. More recently, interest in the use of baclofen as an addiction medicine has grown, with promising preclinical cocaine and amphetamine data and demonstrated clinical benefit from alcohol and nicotine studies. Few preclinical investigations, however, have utilized chronic dosing of baclofen, which is important given that tolerance can occur to many of its effects. Thus the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
2
10
0
2
Order By: Relevance
“…Studies have reported a reduction in efficacy following chronic administration of baclofen and the need to increase the dose to maintain its antispasmodic effect (Heetla et al, 2009; Nielsen et al, 2002). These clinical findings are consistent with the observation that tolerance develops to baclofen's locomotor effects after 5 to 11 days of baclofen in rodents (Beveridge et al, 2013; Gianutsos and K. E. Moore, 1978; Levy and Proudfit, 1977). Interestingly, region-specific reductions in cerebral metabolism were observed in acutely treated rats compared with controls, but not in chronically treated animals (Beveridge et al, 2013).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Studies have reported a reduction in efficacy following chronic administration of baclofen and the need to increase the dose to maintain its antispasmodic effect (Heetla et al, 2009; Nielsen et al, 2002). These clinical findings are consistent with the observation that tolerance develops to baclofen's locomotor effects after 5 to 11 days of baclofen in rodents (Beveridge et al, 2013; Gianutsos and K. E. Moore, 1978; Levy and Proudfit, 1977). Interestingly, region-specific reductions in cerebral metabolism were observed in acutely treated rats compared with controls, but not in chronically treated animals (Beveridge et al, 2013).…”
Section: Introductionsupporting
confidence: 85%
“…These clinical findings are consistent with the observation that tolerance develops to baclofen's locomotor effects after 5 to 11 days of baclofen in rodents (Beveridge et al, 2013; Gianutsos and K. E. Moore, 1978; Levy and Proudfit, 1977). Interestingly, region-specific reductions in cerebral metabolism were observed in acutely treated rats compared with controls, but not in chronically treated animals (Beveridge et al, 2013). These findings emphasized that region-specific changes in neuronal activity must be investigated in order to properly evaluate baclofen's potential as a treatment for conditions that require use of the drug for extended periods.…”
Section: Introductionsupporting
confidence: 85%
“…Alcohol impairs learning and memory in humans and other mammalian organisms [1921]. Thus, quantification of learning and memory may be an efficient method with which alcohol’s effects on brain function may be studied, and with which mutation or drug treatment induced attenuation of the impairing effects may be identified in forward genetic or drug screens.…”
Section: Introductionmentioning
confidence: 99%
“…Dans une étude chez l'animal, en utilisant le modèle murin d'état de stress post-traumatique dont on connaît la comorbidité avec la consommation d'alcool, l'administration de baclofène per os réduirait la prise d'alcool [14], jouant un rôle spécifique dans la diminution de l'activité psychomotrice précédant la prise d'alcool ou craving [15]. L'administration de baclofène aurait égale-ment montré des résultats intéressant dans d'autres addictions : au niveau clinique, réduction du nombre de cigarettes par jour [16], au niveau préclinique avec un rôle possible dans traitement des addictions aux produits psychostimulants [12,17,18], avec une réponse réduite aux amphétamines [12] et à la cocaïne [17].…”
Section: Sur Quel Modèle Psycho-pharmaco-comportemental Repose L'intéunclassified
“…De nombreuses études ont en effet montré une réduction des effets du baclofène au fil du temps avec le développement d'un phénomène de tolérance et la nécessité d'augmenter les doses pour maintenir l'effet théra-peutique [19,20]. Beveridge et al [15] en 2013, dans leur étude chez le rat, trouvent en effet une diminution de cet effet avec l'usage chronique du baclofène, sans épuisement total toutefois au moins au plan fonctionnel puisque la consommation de glucose dans le striatum et le septum reste significativement plus basse, ce qui pourrait expliquer l'effet thérapeutique du baclofène au long cours.…”
Section: Sur Quel Modèle Psycho-pharmaco-comportemental Repose L'intéunclassified